The Impact of Related Party Sales by Listed Chinese Firms on Earnings Informativeness and Analysts Forecasts - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2007)
Using a random sample of 140 China’s listed companies, we show an adverse impact of related party (RP) sales of goods and services on the usefulness of accounting earnings to investors and on earnings forecasts by financial analysts. Consistent with the contention that RP sales may violate the arm’s-length assumption of regular transactions and consequently deteriorate the representational faithfulness and verifiability of accounting data, we find that earnings of firms engaged in RP sales are at least 33% less informative after controlling for known factors that may affect earnings informativeness. We also find that financial analysts behave credulously and provide less accurate and more optimistic earnings forecasts for firms with more RP sales. Overall, our results provide strong empirical evidence on the negative impact of